THE ANTIBACTERIAL ACTIVITY OF CURCUMA XANTHORRHIZA EXTRACT AGAINST ESCHERICHIA COLI ATCC 11229 AND STAPHYLOCOCCUS AUREUS ATCC 25923 - Nur’Aini Purnamaningsih; Hadibah Kalor; Sri Atun (Jurnal Penelitian Saintek, 2017)
The objective of this study were determining the antibacterial activity of Curcuma xanthorrhiza extract with various concentrations of  0,5 ppm, 5 ppm, 50 ppm, 250 ppm, and 500 ppm, and determining the effective concentrations of Curcuma extract antibacterial activity against Escherichia coli ATCC 11229 dan Staphylococcus aureus ATCC 25923. The results showed that the antibacterial activity of Curcuma xanthorrhiza extract with various concentrations of 0,5 ppm, 5 ppm, 50 ppm, 250 ppm, and 500 ppm showed antibacterial activity against Escherichia coli ATCC 11229 and Staphylococcus aureus ATCC 25923. The concentrations of Curcuma xanthorrhiza extract of 500 ppm effective against Escherichia coli ATCC 11229 which the diameter of inhibition by 10,37 mm and Staphylococcus aureus ATCC 25923  by 8,44 mm.